Restructuring urban employment and poverty : the case of Suriname - Menke, Jack (SWI Press ParamariboSR, 1998)
Examines the impact of global and national economic restructuring on urban employment in Suriname from the 1970s to the 1990s as well as the emergent poverty and survival strategies.